2021
DOI: 10.3390/diagnostics11071271
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Evaluation of Pulmonary and Non-Ischaemic Cardiovascular Manifestations of COVID-19

Abstract: Coronavirus Disease 2019 (COVID-19) has been a pandemic challenge for the last year. Cardiovascular disease is the most described comorbidity in COVID-19 patients, and it is related to the disease severity and progression. COVID-19 induces direct damage on cardiovascular system, leading to arrhythmias and myocarditis, and indirect damage due to endothelial dysfunction and systemic inflammation with a high inflammatory burden. Indirect damage leads to myocarditis, coagulation abnormalities and venous thromboemb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 186 publications
(276 reference statements)
0
13
0
Order By: Relevance
“…Nevertheless, viral entry into the respiratory tract and subsequent pneumonia were detected, often worsening to thromboembolism and vessel damage requiring timely treatment for aggressive COVID-19. However, this failed to disentangle the mechanism underlying the SARS-CoV-2 distinct pattern of lung and cardiovascular system changes [ 35 ]. Histologic studies boosted our insight into the complex underlying pathobiology, revealing several vascular features to be relevant, as well as respiratory findings [ 87 ].…”
Section: Pathobiology Of Covid-19: Lung Imaging Foreshadows Vascular ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, viral entry into the respiratory tract and subsequent pneumonia were detected, often worsening to thromboembolism and vessel damage requiring timely treatment for aggressive COVID-19. However, this failed to disentangle the mechanism underlying the SARS-CoV-2 distinct pattern of lung and cardiovascular system changes [ 35 ]. Histologic studies boosted our insight into the complex underlying pathobiology, revealing several vascular features to be relevant, as well as respiratory findings [ 87 ].…”
Section: Pathobiology Of Covid-19: Lung Imaging Foreshadows Vascular ...mentioning
confidence: 99%
“…Firstly, thromboresistance is accomplished to some extent by the presence of natural anticoagulants, including tissue factor pathway inhibitor (TFPI), antithrombin (AT), and thrombomodulin [ 32 , 33 , 34 ]. Secondly, platelet modulators expressed by endothelial cells contribute to thromboresistance via ADP/ATPase on the endothelial cell surface, inhibiting platelet aggregation, the production of nitric oxide (NO) through the action of NO synthase 3 (NOS3) and prostacyclin-2 (PGI-2) via cyclooxygenase (COX) [ 32 , 33 , 34 , 35 ]. Endothelial cells are also critical for vascular integrity and are actively involved in angiogenesis via the inter-endothelial cell junctions [ 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis review of studies of COVID-19 patients developing right ventricular impairment and pulmonary hypertension on mortality concluded that the consensus is that patients who develop PH or RVD through COVID-19 are more likely to die [20]. Similarly, a review by Cicco et al [21] about cardiac imaging evaluation of COVID-19 patients concluded that RV hypertrophy may be caused by mechanical ventilation. The proposed mechanism is that mechanical ventilation can increase RV afterload, causing the RV to thicken in response to increased intrathoracic pressure.…”
Section: Heart Structure Changes In Patients With Covid-19mentioning
confidence: 99%
“…The proposed mechanism is that mechanical ventilation can increase RV afterload, causing the RV to thicken in response to increased intrathoracic pressure. Cicco et al [21] suggest that hypoxic pulmonary vasoconstriction is probably the main factor behind increased arterial pressure.…”
Section: Heart Structure Changes In Patients With Covid-19mentioning
confidence: 99%
“…LUS was identified for this purpose since the pandemic’s beginning. Serial ultrasound examinations on patients with confirmed COVID-19 can promptly detect changes in the affected lung tissue [ 5 , 6 ]. Moreover, many resources have been used to identify an adequate and effective treatment.…”
Section: Introductionmentioning
confidence: 99%